2006
DOI: 10.1159/000090870
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Gemcitabine in BCG-Refractory T1G3 Transitional Cell Carcinoma of the Bladder: A Pilot Study

Abstract: Objective: The aim of this pilot study is to analyze the safety and short-term efficacy of gemcitabine (GEM) as salvage intravesical therapy in a very selected population of bacille Calmette-Guérin (BCG)-resistant T1G3 patients. Methods: 9 recurrent BCG-refractory pT1G3 patients, unsuitable for radical treatment, were treated with GEM, and compared with 10 pT1G3 patients previously treated with at least two courses of transurethral resection plus BGC, with further conservative endovesical BCG administration. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
0
18
0
1
Order By: Relevance
“…The same group of investigators reported a small series of selected BCG-resistant T1G3 patients, unsuitable for radical treatment, who were treated with gemcitabine and compared with 10 pT1G3 patients previously treated with further conservative endovesical BCG administration. 24 Of the 9 patients treated with gemcitabine, 3 were recurrence free after 13, 17, and 21 months, and 7 kept an intact bladder, with an overall survival rate of 100%. Among 10 patients treated with BCG instillation, 1 was recurrence free after 27 months, and 6 kept their bladders, with a survival rate of 80%.…”
Section: Toxicitymentioning
confidence: 94%
See 1 more Smart Citation
“…The same group of investigators reported a small series of selected BCG-resistant T1G3 patients, unsuitable for radical treatment, who were treated with gemcitabine and compared with 10 pT1G3 patients previously treated with further conservative endovesical BCG administration. 24 Of the 9 patients treated with gemcitabine, 3 were recurrence free after 13, 17, and 21 months, and 7 kept an intact bladder, with an overall survival rate of 100%. Among 10 patients treated with BCG instillation, 1 was recurrence free after 27 months, and 6 kept their bladders, with a survival rate of 80%.…”
Section: Toxicitymentioning
confidence: 94%
“…Moreover, we followed the maintenance schedule suggested by Gacci et al 24 Of course, it is clear that no standard regimen exists in this setting, and the optimal frequency and duration of maintenance instillations remain unknown. Thus, further investigation addressing this issue is needed.…”
Section: Toxicitymentioning
confidence: 99%
“…This is lower than in the recent Phase II clinical trial comparing salvage intravesical gemcitabine (33% progression) vs. additional induction BCG (37.5% progression) in patients with recurrent NMIBC despite BCG at 2 years follow-up [11]. The rate of cystectomy was 62% at 5 years which is higher than previously published clinical trials which range from 33% to 56% at a follow-up of 1.5 to 3 years [11][12][13][14][15]. The differences are largely attributable to the fact that in our series we assumed perfect compliance and follow-up as well as strict adherence to NCCN guidelines, which are more aggressive than real-world settings.…”
Section: Discussionmentioning
confidence: 61%
“…The study population of 1300 virtual patients is significantly higher than most published series on BCG refractory patients which range from 20-100 patients [11][12][13][14][15]. Our virtual series contained 58% of patients with clinical stage T1 urothelial carcinoma prior to randomization which falls within the range of previous BCG failure trials where 47%-78% had cT1 tumors [11,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, after further courses, the typical success rate of repeated BCG is <1020%. 41,62,63 After recognizing that BCG exerts its effects via cytokine stimulation, as well as response of type 1 T helper cells (T H 1) and T helper cell recruitment, the addi tion of cytokine therapy to BCG treatment has been tried. For example, IFNα2b functions by enhancing protein TRAIL release, augmenting the T H 1 response, increasing IFNγ release and reducing the expression of inflammationinhibiting proteins such as IL10.…”
Section: Options After Bcg Failurementioning
confidence: 99%